Immobilization of bacteria in microgel grafted onto macroporous polyethylene - Trelles, Jorge Abel (2010)
The development of "Green Chemistry" requires new materials to replace the conventional organic chemistry by biological catalysts, to produce fine chemicals in an environmentally friendly manner. Microbial whole cells can be directly used as biocatalysts, providing a simple and cheap methodology since enzyme isolation and purification are avoided. High-density polyethylene (HDPE) is a very stable polymer though it can be activated by gamma radiation to induce grafting. Glycidyl methacrylate was grafted onto macroporous HDPE and PP in the range of 1-6%, proportional to the initial monomer concentration. Grafted polymers were further chemically modified with ethylenediamine to generate a cationic hydrogel of micron-size thickness onto the internal polymer surfaces. Modified polymers were able to immobilize Gram-positive and Gram-negative bacteria that can catalyze a chemical reaction as efficient as free cells do.